2016
DOI: 10.1128/aac.01842-15
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics/Pharmacodynamics of Peptide Deformylase Inhibitor GSK1322322 against Streptococcus pneumoniae, Haemophilus influenzae, and Staphylococcus aureus in Rodent Models of Infection

Abstract: GSK1322322 is a novel inhibitor of peptide deformylase (PDF) with good in vitro activity against bacteria associated with community-acquired pneumonia and skin infections. We have characterized the in vivo pharmacodynamics (PD) of GSK1322322 in immunocompetent animal models of infection with Streptococcus pneumoniae and Haemophilus influenzae (mouse lung model) and with Staphylococcus aureus (rat abscess model) and determined the pharmacokinetic (PK)/PD index that best correlates with efficacy and its magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Collecting serial blood samples from the same animal (e.g., multiple retro-orbital, facial vein, or tail vein bleeds) at different time points better informs the PK parameters and allows one to separate animal variability from residual error noise (e.g., bioanalytical noise). Serial blood sampling may not be possible in all infection models; however, methods have been developed and employed by some investigators (109–116). Destructive sampling with one PK sample per mouse remains the most common approach.…”
Section: Considerations For Design and Conduct Of In Vivo Pk/pd Modelsmentioning
confidence: 99%
“…Collecting serial blood samples from the same animal (e.g., multiple retro-orbital, facial vein, or tail vein bleeds) at different time points better informs the PK parameters and allows one to separate animal variability from residual error noise (e.g., bioanalytical noise). Serial blood sampling may not be possible in all infection models; however, methods have been developed and employed by some investigators (109–116). Destructive sampling with one PK sample per mouse remains the most common approach.…”
Section: Considerations For Design and Conduct Of In Vivo Pk/pd Modelsmentioning
confidence: 99%
“…In bacteriological studies rats are more frequently used. There are numerous rat models investigating the impact of diabetes ( Oliveira et al, 2016 ), metabolic syndromes ( Feng et al, 2015 ), cirrhosis ( Preheim et al, 1991 ), pharmaco-kinetics and dynamics ( Antonopoulou et al, 2015 ; Hoover et al, 2015 ), intoxication ( Davis et al, 1991 ), immunization ( Iinuma and Okinaga, 1989 ), and general bacterial virulence factors ( Shanley et al, 1996 ) on development of pneumococcal, streptococcal, and staphylococcal pneumonia and lung pathology. Unfortunately, there are only few studies on bacterial and viral co-infections in rats.…”
Section: Suitable In Vivo Models For Mimicking Resmentioning
confidence: 99%
“…The exposure profiles measured in the rats closely matched those reported in humans, with both similar AUC and similar C max values being achieved. PK/PD studies have demonstrated that the AUC correlates with efficacy for GSK1322322 and that the AUCs achieved with these recreated human profiles predict efficacy against S. pneumoniae , H. influenzae , and S. aureus ( 12 ). In fact, the efficacy of the 1,500-mg q12h dosing regimen against skin infections was clinically confirmed in a multicenter, randomized phase IIa trial ( 13 ), thus highlighting the ability of this preclinical model to predict efficacy in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The human exposure profiles recreated in rats were not adjusted for relative differences in protein binding between rat and human since the protein binding values for GSK1322322 and all comparator compounds are similar between the species ( 9 , 12 , 18 22 ). Similarly, the recreated profiles were based on systemic drug levels and do not account for differences in rat and human lung uptake.…”
Section: Discussionmentioning
confidence: 99%